THE INFLUENCE OF SELF-ESTEEM TO SEXUAL BEHAVIOR OF CHRISTIAN GREY AND ANASTASIA STEELE IN EL JAMES’ FIFTY SHADES OF GREY - FANANI, FIBRY HALLA (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: Self-esteem, Sexual Behavior, Social Psychology, Fifty Shades ofGrey. The meaning of self-esteem is individual's sense of his or her value or worth, or the extent to which a person values, approves of, appreciates, prizes, or likes him or herself. For instance, it can be described as a favorable or unfavorable attitude toward the self. Self-esteem is founded in the connection of the sense of competence and worthiness and the relationship between the two as one lives life. In the relationship, self-esteem of individuals strongly effects what kind ofrelationship they might be at. When it comes to sexual encounter, self-esteemdifference between both partners can be seen through their sexual behavior. Thewriter is interested to conduct one main problem, that is how self-esteem influences sexual behavior portrayed in the novel entitled Fifty Shades of Grey by EL James.The writer uses Fifty Shades of Grey novel. Since self-esteem has both psychological and sociological dimensions, both are taken into consideration together in conducting research studies. Hence, socio-psychological approach is vividly used in this research to examine the data about what types self-esteem influence sexual behavior portrayed in the novel.This research reveals that Christian Grey and Anastasia Steele as the main characters in the novel practice dominant-submissive sexual relationship. The writer finds the differences level of self-esteem between Christian Grey and Anastasia Steele. For details, according to the evidences, the writer assumes Christian Grey as the dominant is categorized having higher self-esteem compared to Anastasia Steele as the submissive who is categorized having low self-esteem.The next researcher can analyze different objects from this research. The next researcher also can enrich the theory about self-esteem by using different theory from this research and can make the limitation about the problem of the study.